The role of young scientists in promoting genome editing for sustainable agriculture and food systems in Africa - Kitenge, Seleman Yusuph; Nkhabindze, Bongani; Ratemo, Billy Omboki; Dada, Susan Angira; Ogbimi, Ejeoghene Rita; Karikari, Benjamin; Nuaila, Valter N. A.; Toili, Mary Esther Muyoka; Ndudzo, Abigarl; Adetunji, Charles Oluwaseun; Fotabong, Estherine; Akinbo, Olalekan (Frontiers in Sustainable Food Systems, 2025)
Climate change together with Africa’s growing population, threaten food systems. Improving youth participation in agricultural research and innovation, especially the use of genome editing (GEd) technology, will help address this inequality and ensure that Africa capitalizes on its youth to foster its food systems. This policy brief explores how young scientists are promoting GEd for sustainable agricultural and food systems in Africa. The brief made recommendations to improve on the youth participation in policy making processes and tackling public scepticism to promote the adoption of GEd. It concludes by calling for African governments to make a concerted effort to ensure young scientists are well-informed, supported, and actively involved in the advancement of GEd technology in agriculture in Africa. Climate change and various anthropogenic factors, coupled with Africa’s rapidly growing population, pose significant threats to food systems and the agricultural sector. Challenges such as inadequate youth engagement in agricultural research, lack of funding and a lack of modern infrastructure hinder the continent’s ability to achieve food security. Improving youth participation, particularly in the application of genome editing (GEd) technology, is essential for addressing these disparities and ensuring that Africa leverages its youthful demographic to enhance its food systems. This policy brief explores the pivotal role young scientists play in promoting GEd for sustainable agricultural and food systems in Africa. It highlights specific gaps, such as the need for increased investment in state-of-the-art laboratories, incubators, and mentorship programs, as well as financial assistance and scholarships for aspiring and budding researchers. Furthermore, the brief emphasizes the importance of youth involvement in policy-making processes and the necessity of addressing public scepticism to facilitate the adoption of GEd. By fostering an inclusive environment where young scientists are well-informed and actively engaged, African governments can harness the innovative potential of this demographic to drive agricultural advancements. The brief concludes with a call to action for African governments to prioritize the support and development of young scientists in the advancement of homegrown GEd technology, contributing to the sustainability and resilience of agriculture and food systems across the continent.